Healthier dietary habits are associated with lower depression and anxiety among medical students at a private university in Lima, Peru: A cross-sectional study - Adriana Daniel Armas; Diego S. Polanco Taipe; David R. Soriano-Moreno (PLoS ONE, 2026)
Introduction Anxiety and depression are common conditions among medical students. In recent years, numerous factors associated with these disorders have been investigated; however, evidence regarding the role of dietary habits remains limited. Objective To evaluate the association between dietary habits and the presence of anxiety and depressive symptoms among medical students at a private university in Lima, Peru. Methods An analytical cross-sectional study was conducted in 2025 among medical students aged 18 years and older. Dietary habits were assessed using the Healthy Eating Index, while anxiety and depression were measured using the GAD-7 and PHQ-9 scales, respectively. Poisson regression with robust variance was used to calculate prevalence ratios (PR). Results A total of 264 students were included. Only a minority had healthy dietary habits (1.1%), and the prevalences of anxiety (34.9%) and depression (45.1%) were high. For each additional point in the Healthy Eating Index, the prevalence of anxiety decreased by 3% (aPR: 0.97; 95% CI: 0.95 to 0.98), while the prevalence of depression decreased by 2% (aPR: 0.98; 95% CI: 0.96 to 0.99). Conclusion Dietary habits were inversely associated with the prevalence of anxiety and depression among medical students. These findings highlight the importance of promoting healthy dietary patterns as part of comprehensive strategies for the prevention and promotion of mental health in this population.